Surgical Approach for Uterine Perforation due to Gestational Trophoblastic Neoplasia: A Case Report - Susilo, Sulaeman Andrianto; Homenta, Christian; Mawardinata, Phindo; Sinaga, Ferry Iskandar Kharisma; Suardi, Dodi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: The most common life-threatening complication of gestational trophoblastic neoplasia (GTN) is uterine perforation. In several cases, a surgical approach becomes inevitable. However, there are numerous considerations regarding the technique of hysterectomy.Case Presentation: A 37-year-old (P1A2) woman came to the ER with severe abdominal pain 12 h before admission. The patient had been previously diagnosed with GTN and was scheduled to undergo methotrexate chemotherapy. However, due to the development of an acute abdomen, accompanied by low hemoglobin levels and free fluid showing signs of uterine perforation, an emergency total abdominal hysterectomy was performed. The intra-operative findings revealed intra-abdominal bleeding and uterine perforation at the right fundal side of the uterus. The patient underwent postoperative chemotherapy and showed significant improvement. Conclusion: Regardless of the efficacy of chemotherapy in GTN, abdominal hysterectomy proved to be beneficial for treating uterine perforation in an emergency setting.Pendekatan Pembedahan pada Perforasi Uterus Akibat Tumor Trofoblastik Gestasional : Sebuah Laporan KasusAbstrakPendahuluan: Komplikasi paling umum yang mengancam jiwa dari Tumor Trofoblastik Gestasional (TTG) adalah perforasi uterus. Pendekatan pembedahan tidak dapat dihindari dalam beberapa kasus. Namun, ada banyak pertimbangan mengenai teknik pembedahan dalam setiap kasus.Laporan Kasus: Seorang wanita berusia 37 tahun (P1A2) datang ke UGD dengan nyeri perut hebat 12 jam sebelum masuk rumah sakit. Pasien didiagnosis dengan neoplasia trofoblastik gestasional dan dijadwalkan untuk kemoterapi metotreksat. Abdomen akut, kadar hemoglobin rendah, cairan bebas menunjukkan tanda perforasi uterus. Temuan intraoperatif adalah perdarahan intra-abdomen dan perforasi uterus di sisi fundus kanan uterus. Histerektomi abdomen total darurat dilakukan. Pasien menjalani kemoterapi pasca-operasi dengan kondisi yang membaik.Kesimpulan:Terlepas dari efektivitas kemoterapi pada TTG, histerektomi abdominal bermanfaat untuk mengobati perforasi uterus dalam keadaan darurat.Kata kunci: Histerektomi, perforasi uterus, trofoblastik neoplasia